A computational study of supported Cu-based bimetallic nanoclusters for CO oxidation. Issue 11 (28th February 2018) - Liu, Yulu; Li, Hao; Cen, Wanglai; Li, Jianjun; Wang, Zhengming; Henkelman, Graeme
Abstract : In this study, we used DFT calculations to investigate the bi-functional nature of Cu-based alloy nanoclusters (NCs) supported on CeO2 (111) for CO oxidation. Abstract : In this study, we used DFT calculations to investigate the bi-functional nature of Cu-based alloy nanoclusters (NCs) supported on CeO2 (111) for CO oxidation. More specifically, we studied the reaction pathways on Cu3 Pt7 and Cu3 Rh7 via the O2 associative (OCOO) and dissociative mechanisms. We find that CO oxidation on Cu3 Pt7 proceeds via the O2 dissociation pathway, while Cu3 Rh7 prefers the OCOO mechanism. Combined with our previous results on Cu3 Au7, we find that bi-functional CO oxidation on Cu-based alloys follows a Brønsted–Evans–Polanyi relationship, which provides a useful metric for the design of bi-functional alloyed catalysts.